Valence State of Iron and Molybdenum Cations under Conditions of Anionic Deficiency in Sr2FeMoO6–δ. Issue 3 (27th December 2019) - Kalanda, Nikolay; Yarmolich, Marta; Kim, Dong-Hyun; Baltrūnas, Dalis; Mažeika, Kestutis; Tamulevičius, Sigitas; Andrulevičius, Mindaugas; Sobolev, Nikolai A.
Abstract : The activation energy of oxygen diffusion in strontium ferromolybdate Sr2 FeMoO6– δ is determined by the Merzhanov technique based on the temperature dependences of the oxygen desorption dynamics. The activation energy has a minimum value of 76.7 kJ mol −1 at δ = 0.005 and a maximum value of 156.3 kJ mol −1 at δ = 0.06. It is suggested that with an increase in the concentration of oxygen vacancies, an interaction occurs between them and the nearest cations, with the subsequent formation of associates of various types that are less mobile than the single anion vacancies. According to Mössbauer spectroscopy data, it has been established that the appearance of oxygen vacancies and their ordering contribute to the isomer shift, and some of the iron ions occupy the tetrahedral (or close to it) positions in the lattice. This indicates the formation of associates of oxygen vacancies. The results of X‐ray photoelectron spectroscopy (XPS) studies show that the increase in the concentration of oxygen vacancies results in a decrease of the Mo 6+ and Fe 2+ concentrations. At the same time, the number of Mo 5+ and Fe 3+ cations increases due to the redistribution of the electron density, and molybdenum cations in a different valence state (Mo 4+ ) appear. Abstract : In this article, it is found that an increase in the concentration of oxygen vacancies leads to their association. This process promotes the formation of an intermediate valence state of iron (Fe 2+/3+ ) and causes an increase in the concentration of Mo 5+ /Fe 3+ cations and the appearance of Mo 4+ .